Initial performance of Achillea millefolium in response of humic acids - Altoé Baldotto, Marihus; Gonçalves de Oliveira, Amanda Cristina; da Costa Souza, Aline; Rosário de Souza Dutra, Jéssica; Estrela Borges Baldotto, Lílian (Revista Ceres, 2025)
Owing to numerous health benefits, the cultivation of medicinal plants has significantly increased. Achillea millefolium L. (common names: milefoil, yarrow) is attributed important medicinal properties. Consumers of herbal medicinal products demand for production systems based on ecological farming principles, thus an interesting technology would be application biostimulant based on humic acids. The objective of this study was to evaluate the rooting and initial performance of Achillea millefolium in response to the use of humic acids (HA) isolated from composted cattle manure and poultry litter and applied in different concentrations (0, 10, 20, 30, and 40 mmol L-1 of HA) at the propagation phase. Rooting and plant biomass accumulation were analyzed. Humic acids derived from poultry litter promoted root development and increase of fresh biomass and total dry mass, proving their biostimulant effect. The optimal concentration of humic acids estimated for the initial development of A. millefolium was 22.25 mmol L-1.